INVESTIGATION OF STUDENTS’ PRONUNCIATION OF WORD STRESS IN ENGLISH ONLINE CLASS - Wike Asrianti Prayitno; Dayat Hidayat; Yousef Bani Ahmad (Jurusan Sastra Indonesia, 2022)
The placement of stress also part of learning pronunciation of foreign language. many nonnative English students cannot pronounce the English word in the right way. This study aimed in analyzing students’ pronunciation of word stress in English online class and how do students correct their word stress mistakes. This study was conducted at public Senior High School in Bekasi that involved five participants who agreed to be tested and answered questionnaires. The genders of participants are choosing randomly in eleventh grade. This study found that students still faced difficulties about the pronunciation of word stress. The misplaced stress happened to the two-syllable words, three-syllable words, and four-syllable words. The words most misplaced stress made by students are the three-syllable. The two-syllable words is also the second most misplaced stress made by students. The students’ misplaced stress are quite similar and those words are not difficult because they are quite familiar to be used in conversation. Since the teacher does not pay more attention to word stress in the class, it makes students do not understand how to pronounce clearly, especially the word stress. Students only follow how the words are produced by the teacher during the learning process. Thus, students use the media on their phones to help them correct the mispronunciation of the word stress